The Analysis of the Demographic Bonus Law on Improving Company Employment Relations - Endeh Suhartini; balvas Imantaka; Nur Fitri Melnia; Putri Romadonna; Cayla; Haikal Ikram Arya Ranggana (Journal Equity of Law and Governance, 2024)
Every country has a different population. Residents are all people who live in the territory of a country for six months or more and stay temporarily or permanently for different purposes. Population is very important to support the activities of a country, including to improve the performance of the area where the population lives. The existence of the population is also very important in carrying out a company's performance activities, especially in the implementation of labor relations... At the time of the Demographic Bonus, the age of the productive population dominates compared to the age of the unproductive population. The Demographic Bonus, also known as the "demographic dividend," refers to a period of economic growth that can occur when a country's working-age population (15-64 years old) is larger than the dependent population (children and the elderly). This demographic structure creates a window of opportunity for accelerated economic development because there are fewer dependents to support, allowing for greater investment in education, healthcare, and infrastructure.This research aims to analyze and examine Indonesia's readiness to face the demographic bonus as well as Indonesia's strategy to become a developed country through the momentum of the Demographic Bonus. Based on current data and conditions, Indonesia still needs to prepare everything including strategies that support its progress and avoid everything that brings Indonesia closer to its decline, especially during the Demographic Bonus momentum.